Meningkatkan Kualitas Pendidikan Melalui Pengembangan Kompetensi Sumber Daya Manusia di Bidang Pendidikan - Hayati, Redhatul; Mestika, Yonia; Emelia, Rita; Amra, Abhanda (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to explore and analyze competency development strategies for educational Human Resources (HR) to improve the quality of education in Indonesia. This research uses a qualitative approach through literature study. Data collection is carried out through various literature, namely scientific articles on Google Scholar and reference books. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results showed that the development of educational human resources can be done through on-the-job and off-the-job training strategies and focus on four main teacher competencies: pedagogic, personality, social, and professional competencies. The implications of this research are the need for regular evaluation of Pre-service Teacher Professional Education programs, the implementation of integrated training strategies, adaptation to the VUCA era, and a focus on teacher competency development. This recommendation is expected to make a positive contribution in efforts to improve the quality of education in Indonesia